Corophium volutator - Thacker, Dimple; Patel, Krupal; Myers, Alan; Guerra-García, José M.; Zeidler, Wolfgang; Trivedi, Jigneshkumar (Zenodo, 2023)
196. Corophium volutator (Pallas, 1766) Type locality: Holland. Synomym: Corophium grossipes Linnaeus, 1767; Corophium longicorne Latreille, 1806; Gammarus longicornis Fabricius, 1779; Oniscus volutator Pallas, 1766. Distribution. World: Holland (Pallas 1766), North Atlantic Ocean (Bellan-Santini & Costello 2001), Bay of Biscay (Bachelet et al. 2003), Ireland (Guiry & Guiry 2011), India (Geetha & Nandan 2014). India: Western India Ecoregion: Kerala (Geetha & Nandan 2014). Remark: Report from India requires confirmation. Genus: Monocorophium Bousfield & Hoover, 1997 Published as part of Thacker, Dimple, Patel, Krupal, Myers, Alan, Guerra-García, José M., Zeidler, Wolfgang & Trivedi, Jigneshkumar, 2023, Annotated Checklist of Marine Amphipods (Crustacea: Amphipoda) of India, pp. 1-90 in Zootaxa 5340 (1) on page 63, DOI:10.11646/zootaxa.5340.1.1, http://zenodo.org/record/8324090